Hubungan Kualitas Tidur dengan Kualitas Hidup pada Remaja SMK - Lindawati Lindawati; Wigyo Susanto; Dwi Heppy Rochmawati (Jurnal Ilmu Kesehatan dan Gizi, 2025)
To maintain one's physical, mental, and emotional balance, sleep is a necessary but not sufficient condition. Adolescents' quality of life is profoundly affected by the effects of poor sleep on both their physical and mental health. This research aims to discover how the quality of sleep affects the overall well-being of teenagers enrolled in vocational institutions. The study used a cross-sectional design and was conducted in Banjarnegara's SMK Ma'arif NU 01 Al-Mubarok. The information used in this study came from a survey that was sent out to people. Using the complete sample approach, this research surveyed 90 participating individuals. Data analysis makes use of both bivariate and univariate tests; the latter makes use of the Spearman correlation test in particular. A total of 56 respondents (or 62.2% of the total) reported sleep quality, according to the results of the univariate analysis on the topic of best sleep quality. At the top of the list is quality of life, as 45.6% of the total, or 41 people, said it makes a big difference. According to the presentation, 33 out of the 90 respondents were 16 years old. around 36.7%. With 60 female replies (66.7% of the total), the bulk of the respondents are bezienis. A p-value of 0.000, which is less than 0.005, indicates a significant association between sleep quality and sleep quality, according to the findings of the bivariate analysis using the Spearman rank correlation test. A good night's sleep is strongly correlated with a high quality of life.